Upaya Meningkatkan Minat Baca dan Kemampuan Menyelesaikan Soal Cerita Matematika Kelas II SDN Jurumudi 2 Kota Tangerang - Zuliani, Rizki; Septiliana, Citra; Pihimayatillah, Wapik (MASALIQ, 2023)
This study aims to understand the relationship between reading interest and the ability to solve mathematical problems. This research uses quantitative research methods with the type of survey research. The population in this study were all students of class II SDN Jurumudi 2 Tangerang City with a population of 58 students and a sample of 48 students with a sampling technique using Simple Random Sampling. The research instruments used were questionnaires and essays. Data collection instruments for reading interest (variable X) using a Likert Scale questionnaire with answer choices 1-4 and the ability to solve story problems (variable Y) using essays. To test the hypothesis, it is done by calculating the correlation efficiency with the t test formula. Based on the Product Moment correlation formula with α =0.05 obtained thit 4.290 is greater than ttab = 2.013 that thit> ttab and the hypothesis is accepted. This can be interpreted that there is a relationship between reading interest and the ability to solve math problem class II SDN Jurumudi 2 Tangerang City.